Serological and Molecular Evidence of Q Fever in Domestic Ruminants in Bangladesh - Md. Arifur Rahman; Md. Mahbub Alam; Md. Aminul Islam; A. K. Fazlul Haque Bhuiyan; A. K. M. Anisur Rahman (Veterinary Medicine International)
The objective of this study was to know the herd and animal level prevalence of Q fever in domestic ruminants in some selected districts in Bangladesh. Randomly collected 111 bulk milk and 94 sera samples of cattle, sheep, and goats were tested by indirect ELISA (iELISA). DNA extracted from 23 aborted fetal membranes was analyzed by real time (rt) PCR. The positive cut-off value of iELISA in bulk milk and individual animal sera was ≥30% and ≥40%, respectively. The overall herd level prevalence of Q fever in dairy cattle was 15.6%. The prevalence of Q fever in dairy cattle was significantly higher in Sirajganj in comparison to Satkhira District (P<0.01). The overall seroprevalence of Q fever in domestic ruminants was 5.06%. Although statistically insignificant, the seroprevalence of Q fever was relatively higher in sheep (9.52%) in comparison to goats (3.33%) and cattle (3.57%). Out of 23 aborted fetal membranes, only one sheep placenta was positive in rt PCR. Q fever is present in all of the three important species of domestic ruminants in Bangladesh. It may have some role in sheep abortion as the seroprevalence is relatively higher and also one sheep placenta is rt PCR positive.